The DarkSide-50 outer detectors. Issue 4 (May 2016) - Westerdale, S; Agnes, P; Agostino, L; Albuquerque, I F M; Alexander, T; Alton, A K; Arisaka, K; Back, H O; Baldin, B; Biery, K; Bonfini, G; Bossa, M; et al.
Abstract: DarkSide-50 is a dark matter detection experiment searching for Weakly Interacting Massive Particles (WIMPs), in Gran Sasso National Laboratory. For experiments like DarkSide-50, neutrons are one of the primary backgrounds that can mimic WIMP signals. The experiment consists of three nested detectors: a liquid argon time projection chamber surrounded by two outer detectors. The outermost detector is a 10 m by 11 m cylindrical water Cherenkov detector with 80 PMTs, designed to provide shielding and muon vetoing. Inside the water Cherenkov detector is the 4 m diameter spherical boron-loaded liquid scintillator veto, with a cocktail of pseudocumene, trimethyl borate, and PPO wavelength shifter, designed to provide shielding, neutron vetoing, and in situ measurements of the TPC backgrounds. We present design and performance details of the DarkSide-50 outer detectors.